(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Spiders are a globally distributed group, with established populations in a wide range of habitats. The present study aimed to investigate spider faunal diversity within "Amakoni Reservoir," Sarangarh- Bilaigarh District, Chhattisgarh, India. This study was conducted from December 2024 to November 2025 Specimens were collected from the environs of Amakoni Reservoir (Putka Reservoir) using a variety of collection methods and subsequently identified using a taxonomic key for Indian spiders. This study was conducted to evaluate spider species richness and develop a detailed species checklist for the spider fauna of the Amakoni Reservoir area A total of 23 species, representing 8 families, were recorded from study area. The Araneidae family was the most prevalent, comprising six species. Shannon’s Index (H)=-0.83031 and Simpson’s Index (D)= 0.8425. This research yields significant and contemporary data regarding the species diversity within the "Amakoni Reservoir," Sarangarh- Bilaigarh District, Chhattisgarh and may serve as a useful resource for future research on spider fauna.